(untitled) (Universal International Scientific Journal, 2026)
This article emphasizes the importance of keeping promises and fulfilling every word given. It also emphasizes that keeping promises is not only a personal duty, but also a duty to society. Because, it is argued, if mutual trust is lost in society, the very foundation of humanity will be undermined.